Melhoria na qualidade da prescrição de antineoplásicos em um hospital universitário - Sousa, Carlos Eduardo Pires de (2022)
Antineoplastic drugs are medicines used in the treatment of malignant neoplasms. In general, they have a narrow therapeutic index, with high potential to cause adverse events to the patient when there is an error in its use. The most common errors in the use of antineoplastic drugs are related to prescription, but there are still few studies on the safety of chemotherapy prescription. The aim of this study was to evaluate the effectiveness of a multifaceted intervention in the quality of antineoplastic prescriptions in a Brazilian university hospital. This is a study developed through a nearexperimental design, before-after type, without a control group, using a cycle of quality improvement. This is a study developed through a near-experimental design, beforeafter type, without a control group, with a qualitative approach, using a cycle of quality improvement. The improvement cycle was carried out in the following steps: 1) Identification and prioritization of the quality problem; 2) Analysis of the causes of the problem; 3) Development of quality criteria; 4) Assessment of the level of quality; 5) Quality improvement intervention; 6) Reassessment of the quality level. To evaluate the quality level of the prescription, 60 antineoplastic prescriptions were randomly selected in the institution and the compliance rates of 9 criteria were considered at three different times (1st evaluation, 2nd evaluation and 3rd evaluation). The initial evaluation revealed deficiency in meeting the criteria, especially C1 (correct identification of the patient). After applying a quality intervention based on the training of health professionals and standardization of a prescription model, there was a significant improvement in the fulfillment of 4 criteria analyzed (C1 - correct identification of the patient, C3 - description of the treatment protocol used, C4 - clinical variables for calculating doses and C8 - prescription of supportive care) in the 2nd evaluation, performed immediately after intervention. However, a new evaluation performed after 3 months of the intervention showed a loss of statistical significance of the improvement obtained in criterion 3. This study demonstrated that the proposed improvement cycle was effective and was able to significantly reduce the quality problems of prescriptions for antineoplastic drugs. Additional studies with different methodologies and strategies should be conducted.